Relax : A Practical Guide to Stress-Free Living - Jollands, Beverley (London Southwater, 2000)
Using herbalism, aromtherapy,and other natural therapies to strengthen [hysical and mental well being].
Include Index and Colored Illustrations.
Keywords: Stress (Psychology) -- Stress Management